Direct reference‐free measurement of displacements for railroad bridge management. Issue 10 (3rd August 2018) - Liu, Bideng; Ozdagli, Ali I.; Moreu, Fernando
Summary: Today, railroads carry 40% of the total freight tonnage in North America, and this demand will double in the next 20 years. Half of the North American railroad bridges are over 100 years old. Measuring bridge displacements under train loading can assist in quantifying the safety and reliability of railroad operations. However, obtaining bridge displacements in the field is often challenging due to the lack of fixed reference points. This research studies the direct measurement of reference‐free dynamic displacements using a sensing system composed of one passive‐servo electromagnetic‐induction (PSEMI) velocity sensor and one built‐in hardware integrator unit. The authors used a shake table to quantify the accuracy of the PSEMI sensing system. The shake table replicated various bridge displacements collected in the field under train‐crossing events. The results show that direct reference‐free displacement errors are less than 10% when compared to linear‐variable‐differential‐transducer (LVDT) measurements. The correlation coefficient between measurements is greater than 0.9, indicating the high correlation between the two measurements. The errors are reasonable within standard railroad management scenarios for decision making and bridge prioritization. The indirect estimated displacement (Lee‐method) result shows that it is a structural dynamic parameter‐related approach, because its estimation accuracy depends on the preciseness of the estimated structural dominant period. The conclusions of this study support the use of the PSEMI sensing system as an effective means to measure dynamic displacements of railroad bridges under train loading without a fixed reference or additional computing efforts.